129 Effects of a multi-strain Bacillus subtilis-based direct-fed microbial on growth performance, nutrient digestibility, and colonic pH in diets fed to weanling pigs. (30th November 2020) - Lewton, Jaron R; Woodward, Adrienne; Moser, Ronny; Thelen, Kyan M; Moeser, Adam J; Trottier, Nathalie; Tempelman, Robert; Rozeboom, Dale W
Abstract: A study was conducted to evaluate the effects of a multi-strain Bacillus subtilis-based direct-fed microbial (DFM) on apparent digestibility and colonic pH of nursery pigs. Eighty pigs, of equal number of barrows and gilts (initial BW: 6.99 ± 1.67 kg), were weaned at 21 ± 1 d and randomly allotted to sixteen pens, with five pigs per pen. Two dietary treatments were implemented, a basal control (CON) and a control plus DFM (DFM). Both diets were corn, soybean meal, and distillers dried grains based, formulated to meet all or exceed all nutritional requirements, and manufactured on site. Diets were fed for 42 days. Performance measures were recorded weekly. On d 21 and 42 of the experiment, one pig per pen was randomly selected and euthanized, with equal number of males and females represented. Digestibility of specific nutrients was evaluated within the duodenum, jejunum, ileum, ascending and distal colon. There were no overall differences in growth performance. Overall means ± SD were 0.51 ± 0.05 kg/d, 0.79 ± 0.05 kg/d and 0.66 ± 0.05 for ADG, ADFI, and G:F, respectively. Digestibility of tryptophan within the jejunum tended (P = 0.06) to increase with addition of DFM, as did cysteine (P = 0.12) and methionine (P = 0.10). The analysis also suggested that the impact of the DFM on the digestibility of amino acids may be early in the nursery phase. The pH of contents in ascending colon, a possible indicator of varied fiber digestion, did not differ. Likewise, no differences were observed between treatment in apparent total tract nitrogen and energy digestibility (analysis of distal colon contents). The addition of a multi-strain Bacillus subtilis-based DFM appears to impact digestibility of select amino acids depending upon location in the gastrointestinal tract.